2015
DOI: 10.1111/pan.12626
|View full text |Cite
|
Sign up to set email alerts
|

Anesthetic techniques to facilitate lung lavage for pulmonary alveolar proteinosis in children—new airway techniques and a review of the literature

Abstract: Pediatric patients with pulmonary alveolar proteinosis require whole lung lavage to clear the accumulation of lipoproteinaceous material within the alveoli, to maintain respiratory function. Anesthesia for this presents a challenge due to preexisting respiratory failure, and the small diameter and length of the pediatric airway, which is often unable to accommodate existing one-lung isolation and ventilation equipment. Novel techniques to facilitate lung lavage on seven occasions are described and placed in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 16 publications
0
23
0
Order By: Relevance
“…The smallest double-lumen ETT is 26 French (∼8.7 mm). In infants and small children, different techniques have been proposed [8]: WLL through an elongated cuffed ETT [7] or through a balloon catheter [8,9]; use of two ETTs: a bronchial tube for the lavage and a tracheal tube for ventilation [8,10,11]; WLL via the channel of a flexible bronchoscope with an external diameter of 2.8, 3.5 or 4.9 mm, according to the age of the patient, which allows direct visualisation and more selective lobar lavages (two techniques have been used, one with the bronchoscope being pushed down alongside a narrow ETT, or with it inserted in a large ETT [12][13][14]); and in severely ill children, WLL has been performed under extracorporeal membrane oxygenation [15] or liquid ventilation using polyurethane perflubron [16].…”
Section: Resultsmentioning
confidence: 99%
“…The smallest double-lumen ETT is 26 French (∼8.7 mm). In infants and small children, different techniques have been proposed [8]: WLL through an elongated cuffed ETT [7] or through a balloon catheter [8,9]; use of two ETTs: a bronchial tube for the lavage and a tracheal tube for ventilation [8,10,11]; WLL via the channel of a flexible bronchoscope with an external diameter of 2.8, 3.5 or 4.9 mm, according to the age of the patient, which allows direct visualisation and more selective lobar lavages (two techniques have been used, one with the bronchoscope being pushed down alongside a narrow ETT, or with it inserted in a large ETT [12][13][14]); and in severely ill children, WLL has been performed under extracorporeal membrane oxygenation [15] or liquid ventilation using polyurethane perflubron [16].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, we assume that our method may probably be useful in patients with uneven distribution of ground glass opacities. We are also looking forward to incorporating our method into pediatrics, as our noninvasive approach may be beneficial in patients requiring frequently repeated procedures (25), or when double lumen cuffed intubation is difficult (26).…”
Section: Discussionmentioning
confidence: 99%
“…Lung lavage requires lung isolation to allow simultaneous lavage of one lung and ventilation of the other. Techniques for lung lavage in children are not standardised, all having their own disadvantages and limitations (1). In this case report, we describe a unilateral lung lavage technique in a child with PAP, which has not previously been reported and that may be applicable to other paediatric patients with PAP.…”
Section: Introductionmentioning
confidence: 88%
“…Although some authors reported that they have successfully manipulated lung isolation by placing two cuffed ETTs in each bronchus (5) or by selectively ventilating the non-lavaged lung with a cuffed ETT (6), many others stated that these techniques resulted in intraoperative hypoxemia (1). Furthermore, placing two tubes was not practical and might injure laryngeal structures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation